Strategies and Challenges to Teaching Students with Special Needs During a Pandemic - Roberts, Sarana Eyire; Lee, Yeunjoo (Journal of the American Academy of Special Education Professionals, 2023)
The COVID-19 pandemic has led to immediate school closures resulting in online learning. Online learning under such circumstances has presented challenges for teachers of students with mild to extensive support needs. The current study interviewed twenty special education teachers about the strategies they used when teaching online and the challenges they faced. Teachers discussed several strategies including the use of direct instruction, providing active engagement, caregiver involvement, and their frequent use of informal assessments. Challenges included time constraints and student inattention. Findings of this study can be used to inform strategies to use when teaching students with special needs online and in future online emergency teaching environments.